Buffet diners dining behavior: a proposed preliminary conceptual model - Yusof, Aziz; Othman, Mohhidin; Ghazali, Hazrina; Awang, Khairil Wahidin; Abdul Majid, Mohd Aliff (Human Resource Management Academic Research Society, 2018)
Buffet service popularity lies with its distinct ability to offer ad libitum dining experiences especially when the price regime used pertains to the all-you-can-eat at one price. However, those appeals have been among major issues associated with food waste and overconsumption. In spite of those pressing issues, numerous research works conducted by employing quantitative approaches, so far have not fully captured and explained the underlying determinants behind buffet diners dining behaviors. Therefore, it calls for more qualitative-based research works conducted in this topic area. As part of the reseacher’s qualitative inquiry process, this conceptual paper’s aims are to firstly explore important literatures pertaining to several underlying theories which help to shape the Integrative Behavioral Model (IBM). Following it, the potential of IBM is discussed thus highlighting its potential as an underpinning theory and as a guide in helping to better understand buffet dining behaviors. In doing so, past literatures related to behavioral studies are discussed within the realm of the model’s constructs and its related model extensions as it related to buffet dining situations. At the end, this research paper concludes with future research implication through qualitative inquiry using the proposed preliminary IBM’s conceptual model, taking into considerations the contextual nature of buffet-dining-related behavioural occurrence.